Justicia social y oportunidades laborales de las mujeres del cantón El Guabo provincia de El Oro - Benítez Cruz, Yadira Estefanía (My University, 2019)
This essay exposes the different situations that women have had to go through in order to be included, with the respect, value and recognition that is due, through exploratory, bibliographic reviews, laws are identified within our country that protect and guarantee that all this be fulfilled, even more in the workplace where women currently work on a regular basis. Social justice is important to achieve major changes in women's labor participation such as education and academic training, breaking wage gaps, compliance with laws, equitable remuneration, to understand these changes a detailed bibliographic review was made and exploratory on the insertion of women in the world of work. By providing. A proposal was carried out where women were empowered by making them aware of their rights, giving talks and workshops to raise their self-esteem and better manage the work environment employment opportunities for women, a precedent is set where the change in the thinking of people who tend to discriminate against the work of the female gender can be initiated either by culture, social pressure or by following patterns of behavior within the work. A proposal was carried out where women were empowered by making them aware of their rights, giving talks and workshops to raise their self-esteem and better manage the work environment.
Este ensayo expone las distintas situaciones que ha tenido que atravesar la mujer para lograr ser incluidas, con el respeto, valor y reconocimiento que se merece, a través de revisiones exploratorias, bibliográficas se identifican leyes dentro de nuestro país que amparan y garantizan que todo esto se cumpla, aun mas en el ámbito laboral donde la mujer se desempeña actualmente de manera regular. La justicia social es importante para lograr principales cambios en la participación laboral de la mujer como la educación y formación académica, el rompimiento de las brechas salariales, el cumplimiento de las leyes, la remuneración equitativa, para entender estos cambios se realizó una detallada revisión bibliográfica y exploratoria sobre la inserción de las mujeres en el mundo laboral. Al brindar oportunidades laborales a las mujeres se marca un precedente donde se puede dar inicio al cambio en el pensamiento de las personas que acostumbran a discriminar el trabajo del género femenino ya sea por cultura, por presión social o por seguir patrones de conducta dentro del trabajo. Se llevó a cabo una propuesta donde se logró empoderar a las mujeres haciéndoles conocer sus derechos, emitiendo charlas y talleres para subir su autoestima y manejar de mejor manera el ambiente laboral.
Keywords: JUSTICIA SOCIAL; REMUNERACION; INCLUSION; BRECHA SALARIAL